Profitability of Small-scale Catfish Production in Southwest Nigeria: The challenges (2020)
Challenges, risks and constraints are intrinsic part of any business; fish farming is not an exception. These limit the potential and expected profit of the business. This study analysed the profitability and the challenges limiting the profitability of catfish production in Southwest Nigeria. A 2-stage random sampling procedure was used to select 400 catfish farmers in four randomly selected states in Southwest Nigeria. Structured questionnaire was designed to collect data. Descriptive statistics, Gross margin analysis, Benefit Cost Ratio (BCR) and Expense Structure Ratio (ESR) were used to analyse data. The results show that on the average, size of catfish at harvest was 1.02Kg, production period was 4.37 months, market price was ₦645.45 and the breakeven price was ₦474.43. Also, the total revenue was ₦1,269,961.60, total cost was ₦933,467.98, profit was ₦336,493.62, BCR was 1.36 and ESR was 0.05. Although catfish farming is profitable in Southwest Nigeria, five categories of challenges limiting the profitability of catfish production were identified; profitability, weather, fish diseases and predators, security, and fish marketing challenges. Lack of technical know-how on the part of fish farmers contribute to the severity of business risks and challenges. These challenges have to be thoroughly analysed and adequate plans have to be made to reduce or eliminate their effects on the expected profit and success of the business. Fish farmers should prepare their business plans, analyze the market and evaluate their strengths and opportunities to minimize or eliminate the weaknesses and threats against the success and profitability in catfish business.